Comparative Analysis of Clinical and Functional Results and Position of Intraocular Lens after Femtolaser-Assisted and Standard Cataract Phacoemulsification - I. L. Kulikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Modern surgical treatment of cataracts provides effective results. The study of the position of the intraocular lens (IOL) in the capsule bag can be considered as one of the most important factors influencing the final visual and refractive result of the operation.Aim: comparative analysis of clinical and functional results and position of the IOL in the capsular bag, namely decentration and tilt, when performing femtolazer-assisted phacoemulsification (FLACS) and standard phacoemulsification (CPCS). Materials and methods. We surveyed 57 patients (57 eyes). FLACS was performed in 27 patients, CPCS – in 30 patients. Standard methods of research were used, determination of the position of the IOL (decentration and tilt) in the capsular bag on the device OCT-Casia2 (TOMEY, Germany) and study of wave front were conducted.Results. Comparative analysis of the obtained results showed no significant difference between groups in postoperative visual acuity, however, there was the trend towards higher performance corrected distance visual acuity and uncorrected distance in the group FLACS (0.68 ± 0.18 and 0.74 ± 0.2) compared to the group CPCS (0.58 ± 0.28 and 0.65 ± 0.24). Internal higher order aberrations were significantly low in the group with femtolazer accompaniment: in 3 mm zone almost 2 times (p = 0.041), in 5 mm zone 1.3 times (p = 0.047). Vertical decentration in a CPCS group made 0.217 ± 0.26 mm, in FLACS group – 0.118 ± 0.05 mm, the vertical tilt – 0.75 ± 0.37° and 0.54 ± 0.36 respectively. Conclusion. Decentralizations and IOL tilt tended to lower indices in the FLACS during the observation period up to 2 months after the operation, which was accompanied by lower values of higher order internal aberrations.